If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + 2(-3 + 4g) = 1 + -1g 4g + (-3 * 2 + 4g * 2) = 1 + -1g 4g + (-6 + 8g) = 1 + -1g Reorder the terms: -6 + 4g + 8g = 1 + -1g Combine like terms: 4g + 8g = 12g -6 + 12g = 1 + -1g Solving -6 + 12g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -6 + 12g + g = 1 + -1g + g Combine like terms: 12g + g = 13g -6 + 13g = 1 + -1g + g Combine like terms: -1g + g = 0 -6 + 13g = 1 + 0 -6 + 13g = 1 Add '6' to each side of the equation. -6 + 6 + 13g = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 13g = 1 + 6 13g = 1 + 6 Combine like terms: 1 + 6 = 7 13g = 7 Divide each side by '13'. g = 0.5384615385 Simplifying g = 0.5384615385
| 35313=x(x*0.16) | | 8(6+x)-10(5-4x)=-98 | | -8(-3m-3)-7m= | | m/n=7.3 | | 30=7(y-5)+6 | | 2(3x+5)=76 | | 12(5+2y)=4y-(6-8y) | | -18=c-5 | | -2(7x+1)=14-6x | | 200=xl | | x=35313(35313*0.16) | | 6z+7=5z+6 | | 400/460 | | m-(-18)=7 | | -5x-4-5x=-24 | | 7-3y+6=-7 | | 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 |